Propuesta de una guía que facilite la ruta logística para el reciclaje y transformación de residuos sólidos caseros en el barrio La Candelaria Sector Omaira Sánchez de la ciudad de Cartagena de Indias D.T. y C. (2023)
As the changes increase and the world takes new directions, likewise the countries and their agendas have had to agglomerate in a single feeling and act, focusing on the responsibility of a future and a few generations, who should enjoy certain tools for their stay on planet Earth. That is why the Sustainable Development Goals arise, and with them, try to care for the environment. In this sense, this document presents a proposal that facilitates a logistics route for the recycling and transformation of solid waste in the Omaira Sánchez sector of the La Candelaria neighborhood, knowingly that it is an area where bodies of water connect, to which garbage is thrown. and these, in rainy seasons destroy the waste they find in their path. This is why the research offers a solution and/or comprehensive perspective to a reality of the city of Cartagena in Colombia.